2014
DOI: 10.1108/jopp-14-02-2014-b001
|View full text |Cite
|
Sign up to set email alerts
|

Theory in public procurement research

Abstract: This paper examines the role of theory in public procurement research. Theoretical rigour is integral to management science, yet little is known on the extent and form of theory in public procurement. With the field starting to mature, addressing this issue is timely. From conducting a systematic literature review we find that 29 percent of articles are theoretically grounded, with the incidence of theory having increased in recent years. Economic, sociological, psychological, and management theories are all i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 74 publications
0
72
0
1
Order By: Relevance
“…Second, it addresses the lack of dyadic studies in the field of SSCM (Hall, 2000;Huq, Stevenson, & Zorzini, 2014;Zorzini, Hendry, Huq, & Stevenson, 2015), by examining both buyer and supplier perspectives. Third, relatively few studies concerned with SSCM or public procurement develop theoretical insights (Flynn & Davies, 2014;Touboulic & Walker, 2015;Zorzini et al, 2015), and this study makes a theoretical contribution by adopting resource dependence theory (RDT) (Pfeffer & Salancik, 1978) to guide our study of CBs. Finally, it provides insights for policymakers and buyer and supplier practitioners seeking to implement CBs in a public procurement context.…”
Section: What Are the Factors Influencing The Implementation Of Cbs Imentioning
confidence: 99%
See 1 more Smart Citation
“…Second, it addresses the lack of dyadic studies in the field of SSCM (Hall, 2000;Huq, Stevenson, & Zorzini, 2014;Zorzini, Hendry, Huq, & Stevenson, 2015), by examining both buyer and supplier perspectives. Third, relatively few studies concerned with SSCM or public procurement develop theoretical insights (Flynn & Davies, 2014;Touboulic & Walker, 2015;Zorzini et al, 2015), and this study makes a theoretical contribution by adopting resource dependence theory (RDT) (Pfeffer & Salancik, 1978) to guide our study of CBs. Finally, it provides insights for policymakers and buyer and supplier practitioners seeking to implement CBs in a public procurement context.…”
Section: What Are the Factors Influencing The Implementation Of Cbs Imentioning
confidence: 99%
“…A review of public procurement academic literature reported that less than a third of the articles contained any reference to theory (Flynn & Davies, 2014). Given the dearth of theoretical framing in public procurement research, our aim is to take an established theory to help us better understand the implementation of CBs.…”
Section: Resource Dependency Theorymentioning
confidence: 99%
“…For the further course of this paper, we refer to public procurement as acquisition of goods and services by government of public sector organizations (Uyarra and Flanagan, 2010). At the same time we acknowledge the different factettes in the theoretical field (Brammer and Walker, 2011;Gelderman et al, 2015;Preuss, 2009) and understand within this definition public procurement as a broad field, involving more than the procurement process, but also its potential as a policy tool, its importance for government efficiency, its impacts on innovation and development, as well as the strategic implications it brings along (Flynn and Davis, 2014;Koala and Steinfeld, 2018;Patrucco et al, 2017;Thai, 2008). Adding sustainability to public procurement, we understand public procurement as sustainable when it enfolds the economic, environmental and social dimensions in all public purchases (Brammer and Walker, 2011;Knebel et al, 2019;McCrudden, 2004).…”
Section: Spp and Lack Of A Common Understandingmentioning
confidence: 99%
“…Despite this being a non-exhaustive review, it is clear that there has been little focus placed on public buyers themselves (Flynn & Davis, 2014) in discussion of GPP. So far, affective and habitual elements have emerged as influential individual factors.…”
Section: A Review Of Key Studies Of Green Public Procurementmentioning
confidence: 99%